Treatment outcomes and factors associated with mortality among individuals with both TB and HIV in the antiretroviral era in Thailand - Sivaporn Gatechompol; Kamon Kawkitinarong; Gompol Suwanpimolkul; Pairaj Kateruttanakul; Weerawat Manosuthi; Jiratchaya Sophonphan; Sa.siwimol Ubolyam; Stephen J. Kerr; Anchalee Avihingsanon; Kiat Ruxrungtham (Elsevier, 2019)
Objective: This study aimed to compare treatment outcomes and factors associated with mortality in HIV-1-positive and HIV-1-negative individuals. Methods: We conducted a cohort study between July 2008 and December 2016. Logistic regression was used to determine factors associated with outcomes and death after tuberculosis (TB) treatment. Results: A total of 996 individuals with TB, 228 (22.9%) with HIV-1 co-infection and 770 (77.1%) who were HIV-1 negative were reviewed. The overall treatment success rate was 74.3%. The HIV-1-negative individuals with TB had significantly higher treatment success rates (77.2% vs 64.5%, P>0.001). Using logistic regression analysis, age >50 years (adjusted odds ratio [aOR] 3.89, 95% confidence interval [CI] 2.24-6.76; P>0.001), body weight ≤45kg (aOR 2.19, 95% CI 1.14-4.19; P=0.02) and HIV-1-positive status (aOR 3.31, 95% CI 1.84-5.91; P>0.001) were independently associated with death during TB treatment. Among HIV-1-positive individuals, not undergoing antiretroviral therapy (ART), having diabetes and a CD4 T cell count of >50 cells/mm3 were significantly associated with death. Conclusion: Individuals who had both TB and HIV-1 in Thailand had lower TB treatment success and higher mortality rates compared with individuals with TB without HIV-1. Strategies to improve ART uptake and to reduce risk of developing active TB among individuals with advanced HIV-1 infection should be scaled up.